Ginkgoaleans woods from the jurassic of Argentina: taxonomic considerations and palaeogeographical distribution - Gnaedinger, Silvia Cristina (2011)
A specimen of Baieroxylon rocablanquense nov. sp. from the Roca Blanca Formation (Early Jurassic), and a specimen of Ginkgomyeloxylon tanzanii Giraud and Hankel from the La Matilde Formation (Middle Jurassic), both located in the Santa Cruz province, Argentina, are described in detail. Identification of the morphogenus Baieroxylon is based upon secondary xylem characteristics (cross-field tracheid pitting, cross-fields and ray characters), while identification of Ginkgomyeloxylon is based upon pith, primary xylem and secondary xylem features. A synthesis of Ginkgoalean woods is presented, which combines diagnostic anatomical evidence with data related to stratigraphic and paleogeographical distributions. Based on the results of this analysis, a key for genus-level identification is provided and a new genus, Ginkgopitys, is proposed. These results are used to elucidate global patterns of historical distribution over the course of geological time. In Gondwana, a great diversity of “mixed-type” woods was present during the Mesozoic, especially during the Late Triassic. In contrast, in Laurasia a lower diversity of the mixed-type is recorded for the Paleozoic and Mesozoic, with increases in “abietinoid-type” wood – similar to extant Ginkgo – taking place at the beginning of the Cretaceous. During the Jurassic and Early Cretaceous in both Laurasia and Gondwana, mixed-type and abietinoid-type woods co-existed, illustrating that important evolutionary changes in wood anatomy occurred during the Mesozoic (Jurassic-Cretaceous).